Distribution and Number of Capilong (Calophyllum inophyllum) in Ternate Island of Indonesia - Ishak, Lily; Teapon, Amiruddin; Ashwath, Nanjappa; Hindersah, Reginawanti; Sidayat, Mardiyani (Cannarium, 2021)
Indonesia has a diverse of new and renewable energy sources including biofuels. Biofuels are promising eco-friendly energy sources generated from biological raw materials. Biofuels can also be derived from the seeds of Capilong trees. However, the occurrence of Capilong trees in North Maluku has not been tapped to support a local economic income due to the lack of knowledge of the local community. The present study was undertaken with the aim at investigating the distribution and number of Capilong trees across Ternate Island. A field investigation using a census method was held to collect data on the number and distribution of Capilong trees while observing the following parameters: stage of growth, topography, rock materials and landforms. The findings revealed that Capilong trees are mostly occurred in a tree group, while the seedling population number was low. Interestingly, Capilong trees have demonstrated a natural characteristic that are tolerance to various topography, rock materials and landforms condition. It is therefore recommended to cultivate the plant through a community development program and classify the plant as a potential species that can be used for land rehabilitation programs.